Strengthening Government Administration: A Framework for Enhanced Public Service Delivery and Governance Effectiveness - Natsir Mallawi; Nurasia Natsir (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Background: Government administration plays a crucial role in delivering public services and implementing policies effectively. However, many developing countries face significant challenges in administrative capacity, bureaucratic efficiency, and service delivery quality. Objective: This study aims to analyze the key factors contributing to administrative weaknesses in government and propose a comprehensive framework for strengthening government administration to improve public service delivery and governance effectiveness. Methods: This research employs a mixed-methods approach, combining literature review, case study analysis, and expert interviews. Data was collected from 150 government officials across three administrative levels (national, regional, and local) and analyzed using thematic analysis and statistical methods. Results: The study identified five critical areas for administrative strengthening: (1) Human resource development and capacity building, (2) Digital transformation and technology integration, (3) Process optimization and bureaucratic reform, (4) Performance management systems, and (5) Citizen engagement mechanisms. Implementation of these components showed significant improvements in service delivery efficiency (p < 0.001) and citizen satisfaction scores (p < 0.01). Conclusion: A comprehensive approach to strengthening government administration requires coordinated efforts across multiple dimensions. The proposed framework provides a roadmap for systematic administrative reform that can enhance governance effectiveness and public service quality.